COVID-19 in Turkey: Fewer Applications, More Enrollments - Esen, Oğuz (International Higher Education, 2021)
In Turkey, higher education has been significantly affected by the COVID-19 epidemic. In April 2020, face-to-face education was replaced by distance learning. In 2021, the overall atmosphere of uncertainty affected high school students' applications for admission and preferences, especially low-income students in their senior year, who either postponed their plans for higher education or opted for open education. Demand increased for open education, formal two-year vocational programs, and formal undergraduate education in private universities.